Utility of three‐dimensional transesophageal echocardiography to guide transseptal positioning of a single multistage venous cannula to provide both venous drainage and indirect left ventricular venting in veno‐arterial extracorporeal membrane oxygenation. Issue 11 (2nd October 2020) - Addis, Dylan R.; Wang, Bo; Prejean, Shane P.; Watts, Thomas Evans; Nanda, Navin C.; Ahmed, Mustafa I.
Abstract: A patient with heart failure due to dilated ischemic cardiomyopathy presented in cardiogenic shock for institution of veno‐arterial extracorporeal membrane oxygenation as a bridge to cardiac transplantation. To provide adequate venous drainage and simultaneous decompression of the left atrium (indirect left ventricular venting), a single venous cannula was placed across the interatrial septum so that the distal orifice and side ports were located within the left atrium and the proximal set of side ports were positioned at the cavoatrial junction. Three‐dimensional transesophageal echocardiography demonstrated utility in guiding cannula placement and appropriate positioning within the left atrium.